APPENDIX 3C Digital Image Processing and Analysis with ImageJ. Issue 9 (28th October 2014) - Gallagher, Sean R.
Abstract : ImageJ is a freely available, cross‐platform (e.g., Windows, Mac, Linux) image processing and analysis program developed by the NIH. In addition to being readily available for no cost, ImageJ is supported by a wide range of constantly evolving user‐created functionalities to address a remarkable range of applications, complementing commercial software that typically comes with imaging instruments such as digital gel‐imaging systems or microscopy workstations. New processing/analysis macros and plug‐ins are routinely added to the support site, and are frequently validated via refereed publications. With the continued improvements and growth of fluorescence‐based applications, ImageJ continues to be a mainstay in the laboratory. ImageJ has extensive support materials available online, its base code is regularly updated, and a survey of Medline references indicates that it is one of the most widely used image‐analysis packages available today. © 2014 by John Wiley & Sons, Inc.